UNDERSTANDING EMOTIONAL INTELLIGENCE AND GENDER DIFFERENCES IN ADOLESCENTS POPULATION - Sreelakshmi Menon; Vishnu Jayachandran Nair; Dany Rajakumar; Akhil Raj; Parvathi Gireesh Sandhya (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objective: This study aims to examine emotional intelligence (EI) in adolescents and its gender-based variations influenced by social parameters. Study design: A cross-sectional study Place and Duration: This study was conducted in Kollam City of Kerala India over period of 3 months Methodology: EI was assessed among 500 tenth-grade students using Schutte’s Self-Reported EI Test. Adolescents, aged 14-16 years, were randomly selected from various secondary schools. Random sampling ensured a representative sample of the population. Additionally, a sociodemographic questionnaire was employed to gather relevant background information, including SES, type of school (co-educational or gender-specific), and other contextual variables. Results: EI was impacted by socio-economic status (SES) more in girls than boys (P = 0.003 and P = 0.036, respectively). Co-educational schools showed lower EI compared to gender-specific schools (P < 0.001). EI differences were significant among girls (P = 0.001) but not boys (P = 0.154) based on school type. The type of school attended had a notable impact on EI. Students from co-educational schools had lower EI scores (mean = 116.2, SD = 15.4) compared to those from gender-specific schools (mean = 124.8, SD = 14.2) (P < 0.001). Conclusion: Enhancing SES and integrating mental health components into school health services can improve adolescent EI. Gender-specific EI training programs addressing socio-economic and other contextual issues are recommended for long-term benefits.